Pemberdayaan Masyarakat melalui Pemanfaatan Pangan Lokal untuk Pencegahan Stunting di Papua Barat Daya: Community Empowerment through Local Food Utilization for Stunting Prevention in Southwest Papua - Rumayya Rumayya; Wisnu Wibowo; Titik Puji Rahayu; Onish Akhsani; Wisnu Purnomo; Salsabila Andriana; Yuliance Yunita Bosom Ulim (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Southwest Papua has abundant local food resources; however, they have not yet been optimally utilized by the community. At the same time, stunting prevalence in the region reaches 30.5 percent, exceeding the national average. This community service program aimed to enhance nutritional literacy, local food processing skills, and community food self-reliance through collaboration between Universitas Airlangga, the Sinagi Papua Community, and Green Living Support. The program employed several methods, including a survey of local food plants, food processing training involving 25 indigenous Papuan women from Klatomok, Asbaken, and Malagubtuk villages, and game-based nutrition education for 37 students of SD YPK Maranatha Malagubtuk. In addition, the program resulted in the establishment of Sinagi Papua Food-Lab as a local culinary innovation center. The results indicate improvements in nutritional knowledge, the emergence of small-scale enterprises based on locally sourced flour, and increased community confidence in using local food resources. These findings demonstrate that a local potential–based approach significantly contributes to stunting prevention and to strengthening community economic self-reliance.